Improving Inpatient Services with the Quality Function Deployment Method - Sembiring , Jessyca; Girsang, Ermi; Manalu, Putranto (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2025)
Improvements in the quality of inpatient care are needed to reduce overcrowding, increase patient engagement, make care more efficient, and empower patients toward self-care. These improvements can result in better patient outcomes, increased patient satisfaction, and more efficient delivery of healthcare. This is a quantitative study involving 98 respondents who have used inpatient services at the Royal Prima Hospital between December 2022 and January 2023. Data collection was based on the Servqual method and Kano models. The analysis results show that the smallest gap score (-0.12) is attributed to the number of medical personnel in the reliability dimension, whereas the largest gap score (0.09) is attributed to the physical appearance of doctors and staff in the tangibles dimension. Of the 23 attributes analyzed, 3 belonged to category A (attractive), 15 belonged to category O (one-dimensional), and 5 belonged to category M (must-be). The main technical responses that need to be addressed to improve service quality are hospital development, increased cooperation, and organizing education and training.